Isometric exercises for the strength in the grip of school judokas - Norberto Ávila-Pérez; José Luís González-Ramírez; Luis Alexander Zaldívar-Castellanos (Universidad de Guantánamo, 2018)
It is the result of a diagnostic study of isometric strength, applied to judokas of the school category of the Sports Initiation School "Pedro Díaz Coello". The athlete's preparation plan and current methodological documents were reviewed, and little explanation was found in the methodological guidelines for the development of isometric strength. Methods of scientific knowledge are used, such as analysis-synthesis, historical-logical, survey, measurement, interview and statistical methods. The ontributions obtained in this research are aimed at the development of isometric strength. The form of evaluation of the result is established and the growth times of the isometric force are shown.